2017
DOI: 10.3168/jds.2017-12929
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bleaching agents on the degradation of vitamins and carotenoids in spray-dried whey protein concentrate

Abstract: Previous research has shown that bleaching affects flavor and functionality of whey proteins. The role of different bleaching agents on vitamin and carotenoid degradation is unknown. The objective of this study was to determine the effects of bleaching whey with traditional annatto (norbixin) by hydrogen peroxide (HP), benzoyl peroxide (BP), or native lactoperoxidase (LP) on vitamin and carotenoid degradation in spray-dried whey protein concentrate 80% protein (WPC80). An alternative colorant was also evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…20,21 Hydroxypropyl-bcyclodextrin (HP-b-CD), a hydroxyalkyl derivative of b-cyclodextrin, could enhance the storage stability of astaxanthin/ canthaxanthin by inclusion of astaxanthin/canthaxanthin in HP-b-CD. 22,23 Recent studies also indicated that whey proteins, gelatin or pea protein could deliver various dietary carotenoids, such as a-carotene, 24 astaxanthin, 25 and lutein. 26,27 The object of this study was to select proper wall materials to encapsulate fucoxanthin and improve its stability and bioaccessibility effectively.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Hydroxypropyl-bcyclodextrin (HP-b-CD), a hydroxyalkyl derivative of b-cyclodextrin, could enhance the storage stability of astaxanthin/ canthaxanthin by inclusion of astaxanthin/canthaxanthin in HP-b-CD. 22,23 Recent studies also indicated that whey proteins, gelatin or pea protein could deliver various dietary carotenoids, such as a-carotene, 24 astaxanthin, 25 and lutein. 26,27 The object of this study was to select proper wall materials to encapsulate fucoxanthin and improve its stability and bioaccessibility effectively.…”
Section: Introductionmentioning
confidence: 99%
“…30 Benzoyl peroxide has been used for more than 50 years as a bleaching agent in wheat, cheese and whey processing; benzoyl peroxide destroys the nutrient content of food and produces toxic compounds after reaction with food components, 31 and destroys vitamin A and vitamin B present in food. 32 Chlorine dioxide destroys the vitamin A content during bleaching. 33 Potassium bromate poses a toxic effect on kidneys and thyroid function and increases cancer risk.…”
Section: Ultra-processed Food and Synthetic Nutraceuticals Supplementmentioning
confidence: 99%
“…Alloxan, which is a potent chemical responsible for inducing diabetes mellitus by destroying insulin‐producing cells of the pancreas, 29 is used as a softening agent for ‘refined wheat flour’ 30 . Benzoyl peroxide has been used for more than 50 years as a bleaching agent in wheat, cheese and whey processing; benzoyl peroxide destroys the nutrient content of food and produces toxic compounds after reaction with food components, 31 and destroys vitamin A and vitamin B present in food 32 . Chlorine dioxide destroys the vitamin A content during bleaching 33 .…”
Section: Ultra‐processed Food and Synthetic Nutraceuticals Supplementmentioning
confidence: 99%
“…Chemical bleaching and enzymatic agents are nonspecific oxidative processes that oxidize double bonds of the carotenoid pigment, reducing overall color (Kang et al, 2010). The oxidative process also reduces levels of other carotenoids, such as α-tocopherol, retinol, β-carotene, and α-carotene, and vitamins, such as ascorbic acid (Stout et al, 2017). Several studies have documented that the decolorization of whey using chemical bleaching agents also increases lipid oxida-tion (McDonough et al, 1968;Croissant et al, 2009;Listiyani et al, 2011;Campbell et al, 2012;Smith et al, 2015b).…”
Section: Chemical Bleachingmentioning
confidence: 99%